Contributions on the stability analysis of the simplified dead-time compensator with saturating actuators - Lima, Thiago Alves (2018)
This thesis presents nominal and robust stability analysis of the simplified dead-time compen- sator (SDTC) with actuator saturation for stable and integrative dead-time processes. Such analysis is carried out under LMI framework obtained from the Lyapunov stability and the sector boundedness conditions with performance analysis based on L2 gain. The main advantage of the SDTC is that an anti-windup strategy can be implemented just by addition of the actuator saturation model to the control structure. Tuning procedure along with comparison between the proposed strategy and other anti-windup DTC controllers, including constrained MPC, are discussed with simulation examples. In addition, experimental results on a neonatal intensive care unit are presented in order to validate the usefulness of the SDTC.